Modelling of Data Warehouse Dimensions for AML Systems - Korczak, Jerzy; Oleszkiewicz, Błażej (Advanced Information Technologies for Management – AITM 2009, 2009)
In this article the three main models of data warehouse dimensions (two classical models and hierarchical, based on hierarchical tables) will be evaluated within the context of the use in Anti- -Money Laundering systems. The main focus will be given to a new extension of the Analytical SQL Server: hierarchical tables and vector types used to identify elements in hierarchical tables. A number of examples of time dimension modelling and of Cartesian products computing OLAP will also be presented.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2009; Nr 85, s. 146-159